The 'integrity' of the translated play-text. (2nd January 2019) - Ploix, Cédric
ABSTRACT: This article makes a case for reassessing the 'integrity' (meaning: completeness and condition of being unmarred) of stage-oriented translations as written texts. First, I argue that theatre translations can fully lend themselves to a literary analysis, which leads us to make a case for studying them with a diachronic perspective, and to consider them as historiographical tools. The idea of integrity of translated play-texts, however, faces a major obstacle: not only has the inseparability of text and performance been put forward by a prominent branch of semiotics, but this inseparability is argued to be a fundamental component of the translation process by critics and practitioners. The idea of an 'integrity' (meaning: completeness) of the target text is unquestionably negated in certain types of collaborative practices. After considering some of the main criticisms put forward, the article will envisage cases in which the textual integrity can still be validated. Without altogether refuting these objections, this article still maintains that, at least, the integrity (meaning: unmarred, unviolated) of the target text, in some cases, can be preserved through the processes of collaborative translation.